Greening education: the new millennium - Rolston, Holmes, 1932-2025, author; American Association of State Colleges and Universities, publisher (Colorado State University. Libraries, 2010)
College students today need to be wiser than Socrates, who sought wisdom but avoided nature. John Muir left Wisconsin University for the University of the Wilderness. No education is complete without a concept of nature, and no ethics is complete until one has an appropriate respect for fauna, flora, landscapes and ecosystems. "Who am I?" leads to more inclusive questions: "Where on Earth am I?" "What on Earth ought we to be doing?" Without a three-dimensional education - experience of the urban, the rural, and the wild - students will be under-privileged. The educated person today does not want to live a denatured life, or to live on a denatured planet.
Keywords: ecosystems; nature; public lands; stewardship; environmental ethics; education; sustainable development; sustainable biosphere; value; perpetual perishing